1996
DOI: 10.1007/bf00045106
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic motions of a rigid rotor in short journal bearings

Abstract: In the present paper the conditions that give rise to chaotic motions in a rigid rotor on short journal bearings are investigated and determined. A suitable symmetry was given to the rotor, to the supporting system, to the acting system of forces and to the system of initial conditions, in order to restrict the motions of the rotor to translatory whirl. For an assigned distance between the supports, the ratio between the transverse and the polar mass moments of the rotor was selected conveniently small, with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
119
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(119 citation statements)
references
References 7 publications
0
119
0
Order By: Relevance
“…The required order of the unbalance was only an order of magnitude larger than the technologically acceptable level, thus achievable in the engineering practice. A symmetric rotor system with suitably selected ratio between the transverse and polar mass moments of inertia so as to avoid conical modes of vibration was studied by Adiletta et al [2]. They confirmed numerically the onset of chaos for moderate values of the rotor unbalance.…”
Section: Introductionmentioning
confidence: 92%
“…The required order of the unbalance was only an order of magnitude larger than the technologically acceptable level, thus achievable in the engineering practice. A symmetric rotor system with suitably selected ratio between the transverse and polar mass moments of inertia so as to avoid conical modes of vibration was studied by Adiletta et al [2]. They confirmed numerically the onset of chaos for moderate values of the rotor unbalance.…”
Section: Introductionmentioning
confidence: 92%
“…(1). The model has better accuracy and convergence, and some scholars have proved the reliability of the model [12]. Dimensionless Reynolds equation under the assumption of short bearing is as follows:…”
Section: Dynamic Characteristic Analysis Of a Rotor-bearing Systemmentioning
confidence: 99%
“…In 1994, Brown et al [14] applied short bearing theory to construct a simple model to describe the behaviour of a rigid, hydro dynamically supported journal and showed that the journal behaved chaotically when the rotating unbalance force exceeded the gravitational load. Adiletta et al [15][16][17] performed a series of theoretical and experimental investigations about a rigid rotor supported in short bearings and showed that the rotor performed subharmonic, quasi-periodic and chaotic motions at critical values of the system parameters. Many deterministic physical systems exhibit complex aperiodic behaviour at certain parameter values.…”
Section: Introductionmentioning
confidence: 99%